2017
DOI: 10.1590/s1980-6574201700si0007
|View full text |Cite
|
Sign up to set email alerts
|

Vascular dysfunction in obesity: Beneficial effects of aerobic exercise training in animal models

Abstract: -Cardiovascular disease (CVD) is the leading cause of mortality in the world and several risk factors for developing CVD have been pointed out, including obesity and physical inactivity. Endothelial dysfunction as a consequence of metabolic and inflammatory disorders plays an important role in the onset of vascular complications in obesity. In addition, it is well established that aerobic exercises promote beneficial effects on CVD by increasing nitric oxide (NO) production or its bioavailability in human and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
1
1
1
Order By: Relevance
“…On the other hand, our continuous or interval exercise was effective to improve endothelium-dependent relaxation, even though the exercise sessions were carried out 3 times a week. This result is in agreement with previous findings showing improvement in relaxation response after exercise training sessions performed 5 times a week 9,29,32 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, our continuous or interval exercise was effective to improve endothelium-dependent relaxation, even though the exercise sessions were carried out 3 times a week. This result is in agreement with previous findings showing improvement in relaxation response after exercise training sessions performed 5 times a week 9,29,32 .…”
Section: Discussionsupporting
confidence: 93%
“…In our study, aortas from SD animals showed endothelium-dependent relaxation of about 60%. This response is lower than that found in aortic rings from rats not exposed to fructose intake 26 and is like that observed in femoral rings from animals fed with a high-fat diet 29 . On the other hand, our continuous or interval exercise was effective to improve endothelium-dependent relaxation, even though the exercise sessions were carried out 3 times a week.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation